2010
DOI: 10.1016/j.mce.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cAMP/Epac/PI3K-dependent pathway in the antiproteolytic effect of epinephrine on rat skeletal muscle

Abstract: Very little is known about the signaling pathways by which catecholamines exert anabolic effects on muscle protein metabolism, stimulating protein synthesis and suppressing proteolysis. The present work tested the hypothesis that epinephrine-induced inhibition of muscle proteolysis is mediated through the cAMP/Epac/PI3K-dependent pathway with the involvement of AKT and Foxo. The incubation of extensor digitorum longus (EDL) muscles from rats with epinephrine and/or insulin increased the phosphorylation of AKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 43 publications
5
48
0
4
Order By: Relevance
“…The effect of cAMP on the PI3Kinase pathway has been described to differ between cell types as the two main effectors of cAMP: protein kinase A and EPAC have been reported to have opposing effects on the pathway (Smith et al 2005, Chen et al 2007, Kwak et al 2008, Baviera et al 2010. In the present set of experiments, the effect of cAMP seems to be inhibitory on the FOXO3A/AKT1 phosphorylation.…”
Section: Phosphodiesterases In the Rat Ovarymentioning
confidence: 48%
See 1 more Smart Citation
“…The effect of cAMP on the PI3Kinase pathway has been described to differ between cell types as the two main effectors of cAMP: protein kinase A and EPAC have been reported to have opposing effects on the pathway (Smith et al 2005, Chen et al 2007, Kwak et al 2008, Baviera et al 2010. In the present set of experiments, the effect of cAMP seems to be inhibitory on the FOXO3A/AKT1 phosphorylation.…”
Section: Phosphodiesterases In the Rat Ovarymentioning
confidence: 48%
“…This occurs within 6 h after activation of the pathway (Li et al 2010). It is possible that cAMP interacts with the PI3Kinase pathway through exchange protein directly activated by cAMP (EPAC) in the oocyte as seen in skeletal muscle (Baviera et al 2010). Alternatively, cAMP may increase the production of Kit ligand (KITLG), also known as stem cell factor, in the granulosa cells (GC) as gene expression of KITLG has been shown to be stimulated by cAMP in Sertolli cells, and in ovarian cancer cells (Shaw et al 2002, Grimaldi et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…26,47 Interestingly, an important role for the PI3K/AKT pathway has been shown to stimulate FOXO3A and FOXG1 phosphorylation via epinephrine or IGF1, respectively. 9,49 The PI3K/AKT pathway is also known to be important as an amplification signaling pathway for initial platelet activation via epinephrine 50 and ADP. 51 Further studies are needed to define whether FOXG1 is also essential in this pathway to obtain full platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly however, they reported that a PI3K inhibitor wortmannin also inhibited cAMP-analogue enhanced eosinophil survival. Even though the PI3K-Akt pathway is not classically considered as a signalling pathway of β 2 -agonists and cAMP-elevating agents, it is tempting to speculate, that β 2 -agonist mediated eosinophil survival could follow β-receptoradenylyl cyclase -cAMP -PKA -PI3K -Akt pathway as recent reports suggest [25][26][27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%